Implementasi Program Jaminan Kesehatan Medan Berkah (JKMB) pada Pengemis di Kota Medan - Cicilia Kimberly Oldy Saragih; Fajar Utama Ritonga (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Equal access to health services is a fundamental right of citizens. However, vulnerable groups such as beggars are often neglected because they do not have valid residence documents. The Medan City Government launched the Medan Berkah Health Insurance Program (JKMB) to support universal Health Coverage, allowing free health services only with a Medan ID card. This study aims to assess the implementation of JKMB on beggars in Medan City by using the implementation suitability model from David C. Korten, which emphasizes the relationship between programs, organizations, and beneficiaries. The method used is a descriptive qualitative approach, with data collection through in-depth interviews, observations, and documentation studies. Informants consisted of beggars without identity who had been disciplined by Social Services, program Implementation officers, and academics in the field of social welfare. The results showed that JKMB can only be accessed by beggars while under the supervision of Social Services, through temporary identities such as